Design and Analysis of Robust Kanban System in an Uncertain Environment - Li, Zhe (Wissenschaftliche Berichte des Institutes für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2013)
Kanban is a representative control policy pursuing cost-efficient features for the material flow system. However, the Kanban mechanism increases the system vulnerability especially when the environment is uncertain. Therefore, we proposed a robust Kanban system model for the supply chain system based on the Kanban mechanism. The model can use robust approaches from strategic, tactical, and operational levels to deal with the risks in an uncertain environment.